The Concept and Historical Reality of Islamic Politics in Responding to Democracy - Soleh, Nurrohman Muhamad; Subakti, Ganjar Eka (FALASIFA : Jurnal Studi Keislaman, 2024)
This research aims to analyze Islamic views and responds towards the concept of democracy based on the ideal concept and historical reality of Muslim politics. This research uses a qualitative method with a narrative approach and uses literature studies in data collection techniques. Islamic views on the concept of democracy are divided into two groups, namely groups that reject and accept democracy as a state system. The group that rejects the concept of democracy has the argument that the concept of democracy is contrary to Islamic teachings, and the sovereignty of God is the highest power compared to the sovereignty of the people. Meanwhile, the accepting group has an argument that democracy is in harmony with Islamic teachings and the implementation of democracy is permitted as long as it does not conflict with Islamic law. Meanwhile, based on the political reality of Muslims, the implementation of democracy is closely related to the cultural and political conditions of Islamic- majority countries, where in some Islamic-majority countries democracy is rejected as a system of government, but on the other hand democratization is rapidly developing into a system of government in several other Islamic- majority countries.